Increase of Intracellular Cyclic AMP by PDE4 Inhibitors Affects HepG2 Cell Cycle Progression and Survival. Issue 6 (30th November 2016) - Massimi, Mara; Cardarelli, Silvia; Galli, Francesca; Giardi, Maria Federica; Ragusa, Federica; Panera, Nadia; Cinque, Benedetta; Cifone, Maria Grazia; Biagioni, Stefano; Giorgi, Mauro
ABSTRACT: Type 4 cyclic nucleotide phosphodiesterases (PDE4) are major members of a superfamily of enzymes (PDE) involved in modulation of intracellular signaling mediated by cAMP. Broadly expressed in most human tissues and present in large amounts in the liver, PDEs have in the last decade been key therapeutic targets for several inflammatory diseases. Recently, a significant body of work has underscored their involvement in different kinds of cancer, but with no attention paid to liver cancer. The present study investigated the effects of two PDE4 inhibitors, rolipram and DC‐TA‐46, on the growth of human hepatoma HepG2 cells. Treatment with these inhibitors caused a marked increase of intracellular cAMP level and a dose‐ and time‐dependent effect on cell growth. The concentrations of inhibitors that halved cell proliferation to about 50% were used for cell cycle experiments. Rolipram (10 μM) and DC‐TA‐46 (0.5 μM) produced a decrease of cyclin expression, in particular of cyclin A, as well as an increase in p21, p27 and p53, as evaluated by Western blot analysis. Changes in the intracellular localization of cyclin D1 were also observed after treatments. In addition, both inhibitors caused apoptosis, as demonstrated by an Annexin‐V cytofluorimetric assay and analysis of caspase‐3/7 activity. Results demonstrated that treatment with PDE4 inhibitors affected HepG2 cell cycle and survival, suggesting that they might be useful as potential adjuvant, chemotherapeutic or chemopreventive agents in hepatocellular carcinoma. J. Cell. Biochem. 118: 1401–1411, 2017. © 2016 Wiley Periodicals, Inc. Abstract : A significant body of work has underscored the involvement of PDE4, a cyclic AMP hydrolyzing enzyme, in different kinds of cancer, with no attention paid to liver cancer. The present study investigated the effects of two PDE4 inhibitors, rolipram and DC‐TA‐46, on the growth of human hepatoma HepG2 cells. Results demonstrated that these inhibitors affected HepG2 cell cycle and survival, suggesting that they might be useful as potential adjuvant, chemotherapeutic, or chemopreventive agents in hepatocellular carcinoma.